2010
DOI: 10.1021/ef100801e
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency Waste-to-Energy Plants − Effect of Ash Deposit Chemistry on Corrosion at Increased Superheater Temperatures

Abstract: Thermodynamic modeling has been used to study the ash deposit chemistry in waste-fired power plants and the implications for corrosion for increased superheater temperatures. Melting of ash particles and deposits can increase the corrosion of the superheater tubes due to molten salt corrosion. Predictions were made for various waste fuel mixtures with varying contents of Na, K, Pb, Zn, Cl, and S at superheater temperatures (350−550 °C). The results show that the formation of a low-melting, chloride-rich melts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Several studies reported gas-phase sulfation of alkali chlorides during the biomass combustion, aiming to reduce the amount of sticky alkali chlorides in the flue gas. On the other hand, the formation of low-melting-point acidic alkali sulfates, such as K 2 S 2 O 7 and KHSO 4 , were also reported when the SOx concentrations in the flue gas were high. , In this case, the deposited alkali sulfates (such as K 2 SO 4 and Na 2 SO 4 ) are further sulfated with the presence of SO 3 and lead to the formation of low-melting-point alkali pyrosulfates (Na 2 S 2 O 7 with mp 389 °C, and K 2 S 2 O 7 with mp 404 °C) . However, the solid-state sulfation of alkali chlorides is believed to be slow and is only important in the deposits and not in the fly ashes .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported gas-phase sulfation of alkali chlorides during the biomass combustion, aiming to reduce the amount of sticky alkali chlorides in the flue gas. On the other hand, the formation of low-melting-point acidic alkali sulfates, such as K 2 S 2 O 7 and KHSO 4 , were also reported when the SOx concentrations in the flue gas were high. , In this case, the deposited alkali sulfates (such as K 2 SO 4 and Na 2 SO 4 ) are further sulfated with the presence of SO 3 and lead to the formation of low-melting-point alkali pyrosulfates (Na 2 S 2 O 7 with mp 389 °C, and K 2 S 2 O 7 with mp 404 °C) . However, the solid-state sulfation of alkali chlorides is believed to be slow and is only important in the deposits and not in the fly ashes .…”
Section: Resultsmentioning
confidence: 99%
“…The Equilib module of Factsage calculates the phase assemblage and phase composition of a multicomponent and multiphase system at the lowest Gibbs energy, based on the specified conditions and included thermodynamic databases. 28 All input data in the equilibrium model are based on experimental data and operational data obtained during the fullscale measurements. Therefore, it is possible to compare the experimental findings with the theoretical calculations and thus evaluate the accuracy of the thermodynamic model for the fouling prediction.…”
Section: Energy and Fuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boilers utilizing wastes, prone to significant corrosion and degradation of components in different operating environments, are well-documented [30]. Corrosion from alkali-chlorides is also significant in such boilers and is often further complicated if demolition wood from old buildings or railroad beams, with appreciable content of metals like lead and zinc, is used [31,32]. Similarly, the black liquor recovery boilers (BLRBs) are also beset with problems of corrosion [33].…”
Section: Corrosion Protection Coatingsmentioning
confidence: 99%